The quality function of distribution Method is Used to Improve the Quality of Education - Kelesbayev, D.N.; Ersoy , Abdullah (BUKETOV BUSINESS REVIEW, 2017)
Improving and improving the quality of educational activities is one of the most important issues of the educational system, as in all other systems. Compared with the indicators of the quality of education at the international level, improving and improving the quality of education in the Republic of Kazakhstan requires a long time and great efforts. To promote research and development in this field and direction, which are the most important, to improve and improve the educational system of the Republic of Kazakhstan, the application of the QFD method (distribution of the quality function), which regards the education system as a single whole, is being investigated. This research work is theoretical, the theoretical application of the QFD method in higher education institutions is shown. Much attention is also paid to the rational use of the QFD method. Provided comprehensive theoretical and applied data on the method, positive results in improving the quality of educational activities in higher education. The proposed method can be used in higher education institutions, as well as the educational system of the Republic of Kazakhstan.